Well-being and climate change: Evidence for Portugal - Souza-Jr., Ary José A. (European Scientific Journal, ESJ, 2022)
This paper analyses the impact of air pollution, climate conditions, and extreme weather events on subjective well-being in Portugal, based on a regional analysis, through the estimation of an ordered probit model. The estimation applies data at the individual level from the 8th and 9th waves of the European Social Survey, along with an air quality indicator, environmental variables, national forest inventory, and a study about the possible future effects of the sea-level rise on vulnerable areas and people living therein. Even after controlling for socio-economic variables and personal traits, the results suggest the existence of differences between regional welfare levels. Air pollution has a negative impact on life satisfaction due to its bad impacts on health (aggravating the condition of individuals with heart and lung diseases). The paper’s key finding is to show that at the regional level, both past (forest fires) and «possible» future (floods due to sea-level rise) extreme weather events may impact the current welfare level. Also, assessments of implicit willingness do to pay demonstrate that climate change effects have a relevant impact on their quality of life nowadays.